The level of proteinuria and the state of endothelial function in patients with chronic kidney disease combined with subclinical hypothyroidism under the influence of combined antihypertensive therapy. - O. V. Kuryata; I. P. Garmish (Medičnì Perspektivi, 2018)
Our aim was to assess the level of proteinuria and changes in vascular endothelial function in patients with chronic kidney disease (CKD) in combination with subclinical hypothyroidism (SHT) under the influence of antihypertensive combination therapy (valsartan 160 mg and amlodipine 5 mg). We examined 48 patients with CKD I-II stages and AH 1 and 2 degrees. Depending on the functional state of the thyroid gland, patients were divided into 2 groups. Within 12 weeks patients took a fixed combination of amlodipine 5 mg and valsartan 160 mg. Target BP levels were achieved in 19 (86.3%) patients of the main group and 22 (84.6%) of the comparison group. More often violation of brachial artery flow-mediated dilation and higher level of daily proteinuria were found in the main group patients. At the end of the study, the level of daily proteinuria in the main group decreased by 46.03% (p<0.01), and in the comparison group – by 55.3% (p<0.01). SHT can be considered as an additional factor that affects the course of CKD and AH by worsening the state of endothelial function and increasing the level of daily proteinuria. Combination of valsartan 160 mg and amlodipine 5 mg has lead to achieving of target blood pressure levels, improving of endothelial function and decreasing of daily proteinuria in both groups.